Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s11547-008-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of advanced MR imaging modalities in diagnosing cerebral gliomas

Abstract: The objective of this study was to evaluate the potential role of newly developed, advanced magnetic resonance (MR) imaging techniques (spectroscopy, diffusion and perfusion imaging) in diagnosing brain gliomas, with special reference to histological typing and grading, treatment planning and posttreatment follow-up. Conventional MR imaging enables the detection and localisation of neoplastic lesions, as well as providing, in typical cases, some indication about their nature. However, it has limited sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Several authors have demonstrated the usefulness of employing short TE (35 msec) rather than long TE (144 msec) sequences on high-field MR spectroscopy in grading cerebral gliomas, when only the intratumoral region was taken into account [26]. This was also confirmed from our study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several authors have demonstrated the usefulness of employing short TE (35 msec) rather than long TE (144 msec) sequences on high-field MR spectroscopy in grading cerebral gliomas, when only the intratumoral region was taken into account [26]. This was also confirmed from our study.…”
Section: Discussionsupporting
confidence: 85%
“…In particular, in highgrade gliomas, Cho was elevated in the peritumoral edema, while NAA was reduced in the periphery [26]. Similarly, Server et al, using long TE (135 msec) 1 H-MRS, observed elevation in peritumoral Cho/Cr and Cho/NAA metabolic ratios in relation to grading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that apparent diffusion coefficient (ADC) maps, which indicate the magnitude of the diffusion of water molecules within cerebral tissue obtained from several diffusion‐weighted images, may be useful for preoperative grading . However, the role of ADC maps in differentiating between low‐grade and high‐grade gliomas has been disputed . A number of studies have shown that reduced ADC values can be clearly detected in high‐grade gliomas .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies investigating the capacity of MRI to delineate the tumor boundaries of gliomas are scarce. Some studies used image-guided tumor biopsy or postmortem specimens for correlation and reported on discrepancies between the real tumor extent and findings by MRI (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%